PENGARUH PERUBAHAN FAKTOR EKSPOSI TERHADAP NILAI CT NUMBER - Tina Melinda; Eko Hidayanto; Zaenal Arifin (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
CT Number valuehad been conducted with various of exposurefactoronCT. Testingwas conducted to test the CTNumber value changeswith varioues of exposure factorsthencompare it withthe recommendedtolerance. Testing was doneby usingsome objectthere arewater phantom, plasticwaterphantom, chickenblood, chicken (breast part) andchickenbone(thigh). Performedwithtwoscanning, axialandhelicalscanning methods. Various of exposurefactors used the voltage 80 kVp to 140kVp, current100 mA to 180mAandexposure time0.6 second to 2second. Collimatorwith alargeselection and slice thickness 5mm. From the test resultshave known thatchangesof the exposurefactorswill affectedCTNumber value. CT Number value obtain from the test results by using water phantom -2,50 HU until -4,99 HU, plastic water phantom -6,99 HU until +6,99 HU, blood +31,01 HU until +36,70 HU, chiken (soft tissue) +48,33 HU until +66,61 HU and bone +800,15 HU until +1188,28 HU.Thevalue is stillwell withinthe recommendedtolerancesareforwater phantom andplasticwaterphantom0±7HU, blood+30 HU to+45HU, soft tissue+37 HUto+300 HU andbone+700HUto+3000 HU.Keywords: CTNumber, exposure factors, plasticwaterphantom, axial scanning andhelicalscanning